Market mapping for improved cookstoves: barriers and opportunities in East Africa. Issue 1 (2nd January 2020) - Stevens, Lucy; Santangelo, Edoardo; Muzee, Kennedy; Clifford, Mike; Jewitt, Sarah
ABSTRACT: The East African region has been a hub for the development and marketing of improved cookstoves since the 1980s. However, there are differences in the rates of uptake of stoves between Kenya, Uganda and Tanzania. This article uses a participatory approach to market mapping, identifying the key barriers to market growth. The findings illustrate common barriers of access to finance, but also differences between the countries in their stove value chains and enabling environments. Participatory use of market mapping techniques would help to catalyse further action at the national level.